Growing old in a new China : transitions in elder care - Keimig, Rose K. (Global perspectives on aging, 2021)
Growing Old in a New China: Transitions in Elder Care is an accessible exploration of changing care arrangements in China. Combining anthropological theory, ethnographic vignettes, and cultural and social history, it sheds light on the growing movement from home-based to institutional elder care in urban China. The book examines how tensions between old and new ideas, desires, and social structures are reshaping the experience of caring and being cared for. Weaving together discussions of family ethics, care work, bioethics, aging, and quality of life, this book puts older adults at the center of the story. It explores changing relationships between elders and themselves, their family members, caregivers, society, and the state, and the attempts made within and across these relational webs to find balance and harmony. The book invites readers to ponder the deep implications of how and why we care and the ways end-of-life care arrangements complicate both living and dying for many elders.